#### Answer

234 poles

#### Work Step by Step

We have a sequence with:
$a_1=25$
$a_2=24$
$a_3=23$
$a_n=26-n$
So:
$a_{12}=26-12=14$
To find the sum, we use:
$S_n=\frac{n}{2}(a_1+a_n)$
$S_{12}=\frac{12}{2}(a_1+a_{12})$
$S_{12}=6(25+14)=39*6=234$

Published by
Brooks Cole

ISBN 10:
1305115546

ISBN 13:
978-1-30511-554-5

234 poles

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.